Progress toward universal health coverage in ASEAN - Hoang Van Minh; Nicola Suyin Pocock; Nathorn Chaiyakunapruk; Chhea Chhorvann; Ha Anh Duc; Piya Hanvoravongchai; Jeremy Lim; Don Eliseo Lucero-Prisno III; Nawi Ng; Natalie Phaholyothin; Alay Phonvisay; Kyaw Min Soe; et al. (Taylor & Francis Group, 2014)
Background: The Association of Southeast Asian Nations (ASEAN) is characterized by much diversity in terms of geography, society, economic development, and health outcomes. The health systems as well as healthcare structure and provisions vary considerably. Consequently, the progress toward Universal Health Coverage (UHC) in these countries also varies. This paper aims to describe the progress toward UHC in the ASEAN countries and discuss how regional integration could influence UHC. Design: Data reported in this paper were obtained from published literature, reports, and gray literature available in the ASEAN countries. We used both online and manual search methods to gather the information and 'snowball' further data. Results: We found that, in general, ASEAN countries have made good progress toward UHC, partly due to relatively sustained political commitments to endorse UHC in these countries. However, all the countries in ASEAN are facing several common barriers to achieving UHC, namely 1) financial constraints, including low levels of overall and government spending on health; 2) supply side constraints, including inadequate numbers and densities of health workers; and 3) the ongoing epidemiological transition at different stages characterized by increasing burdens of non-communicable diseases, persisting infectious diseases, and reemergence of potentially pandemic infectious diseases. The ASEAN Economic Community's (AEC) goal of regional economic integration and a single market by 2015 presents both opportunities and challenges for UHC. Healthcare services have become more available but health and healthcare inequities will likely worsen as better-off citizens of member states might receive more benefits from the liberalization of trade policy in health, either via regional outmigration of health workers or intra-country health worker movement toward private hospitals, which tend to be located in urban areas. For ASEAN countries, UHC should be explicitly considered to mitigate deleterious effects of economic integration. Political commitments to safeguard health budgets and increase health spending will be necessary given liberalization's risks to health equity as well as migration and population aging which will increase demand on health systems. There is potential to organize select health services regionally to improve further efficiency. Conclusions: We believe that ASEAN has significant potential to become a force for better health in the region. We hope that all ASEAN citizens can enjoy higher health and safety standards, comprehensive social protection, and improved health status. We believe economic and other integration efforts can further these aspirations.